2015
DOI: 10.1590/0037-8682-0105-2013
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites as a largely neglected problem in the Brazilian Amazon: highlights of the epidemiological trends in the State of Amazonas

Abstract: 34www.scielo.br/rsbmt I www.rsbmt.org.br Revista da Sociedade Brasileira de Medicina Tropical 48(Suppl I):34-41, 2015http://dx.doi. org/10.1590/0037-8682-0105-2013 Review Article ABSTRACT Envenoming snakebites are thought to be a particularly important threat to public health worldwide, especially in rural areas of tropical and subtropical countries. The true magnitude of the public health threat posed by snakebites is unknown, making it diffi cult for public health offi cials to optimize prevention and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 12 publications
9
85
0
11
Order By: Relevance
“…In the Brazilian Amazon, although urban population predominates, most of the snakebites were recorded in adult males living in rural areas. This epidemiological profile was reported previously in the Amazon (35,36), and probably is related to a significant higher exposition of this population group when exerting agricultural or forestry activities, in the habitat mostly selected by lancehead pit vipers. Several studies have reported on habitat use by B. atrox, the easiest snake to find in comparison to other species in Central Amazonia (46), and concluded that the species is mainly found on the ground or climb into understory vegetation, in the case of juveniles (15)(16)(17).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the Brazilian Amazon, although urban population predominates, most of the snakebites were recorded in adult males living in rural areas. This epidemiological profile was reported previously in the Amazon (35,36), and probably is related to a significant higher exposition of this population group when exerting agricultural or forestry activities, in the habitat mostly selected by lancehead pit vipers. Several studies have reported on habitat use by B. atrox, the easiest snake to find in comparison to other species in Central Amazonia (46), and concluded that the species is mainly found on the ground or climb into understory vegetation, in the case of juveniles (15)(16)(17).…”
Section: Discussionsupporting
confidence: 83%
“…In the Brazilian Amazon, snakebites are under the influence of precipitation, likely because snakes in the Amazon exhibit increased activity during months with heaviest rainfall. Moreover, in this period, the snakes look for upland areas during flooding, which increases the likelihood of contact between humans and snakes (35,36). The contact between snakes and human populations is often associated with extractive or agricultural activities, which can increase snakebite burden in…”
Section: Introductionmentioning
confidence: 99%
“…The review by Feitosa et al (11) systematically addresses snake bites as one of the most neglected problems in the Amazon region. This review demonstrates the magnitude of this type of envenoming in a background of lack of information, calling for a more aggressive approach by the authorities and affected communities to implement an appropriate surveillance system and promote the reduction of risk in the affected populations as well as ensuring access to timely treatment.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This review demonstrates the magnitude of this type of envenoming in a background of lack of information, calling for a more aggressive approach by the authorities and affected communities to implement an appropriate surveillance system and promote the reduction of risk in the affected populations as well as ensuring access to timely treatment. Despite the low mortality registered, the sequelae of severe poisoning are important and timely treatment would reduce both harmful sequelae and mortality (11) .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Information systems with a good performance are needed for adequate surveillance of the number of accidents per geographical region, types of venom, and the consequences of the bites (2) . Records of these accidents are useful to reduce the incidence by promoting health education and to decrease their severity, frequency of sequelae, and lethality (4) .…”
mentioning
confidence: 99%